2020
DOI: 10.3389/fimmu.2020.02039
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk Between the MSI Status and Tumor Microenvironment in Colorectal Cancer

Abstract: Colorectal cancer (CRC) patients, especially those with deficient mismatch repair (dMMR)/microsatellite instability-high (MSI-H) tumors, whose sensitivity to immune checkpoint inhibitors (ICIs) is significantly higher than that of patients with microsatellite-stable (MSS)/microsatellite instability-low (MSI-L) tumors, have derived clinical benefits from immunotherapy. Most studies have not systematically evaluated the immune characteristics and immune microenvironments of MSI-H and MSS/MSI-L CRCs. We analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
184
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(193 citation statements)
references
References 50 publications
7
184
0
2
Order By: Relevance
“…As additional bases insertion or existing bases deletion from microsatellites, DNA mismatch errors occur during DNA replication, which can be supervised and corrected by the MMR system ( Arana and Kunkel, 2010 ). For patients with MMR deficiency (dMMR), accumulated mismatch mutation and frameshift mutation will lead to the MSI phenotype, neoantigens production, and is related to carcinogenesis of several cancers, such as CRC, gastric cancer, pancreatic cancer, and endometrial cancer ( Palomaki et al, 2009 ; Seo et al, 2009 ; Ghidini et al, 2020 ; Lin et al, 2020 ). In CRC, dMMR or high levels of MSI (MSI-H) were correlated with high TMB and immunocyte infiltration, which made dMMR-MSI-H CRC responsible for ICBs ( Alexander et al, 2001 ; Llosa et al, 2015 ; Ganesh et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…As additional bases insertion or existing bases deletion from microsatellites, DNA mismatch errors occur during DNA replication, which can be supervised and corrected by the MMR system ( Arana and Kunkel, 2010 ). For patients with MMR deficiency (dMMR), accumulated mismatch mutation and frameshift mutation will lead to the MSI phenotype, neoantigens production, and is related to carcinogenesis of several cancers, such as CRC, gastric cancer, pancreatic cancer, and endometrial cancer ( Palomaki et al, 2009 ; Seo et al, 2009 ; Ghidini et al, 2020 ; Lin et al, 2020 ). In CRC, dMMR or high levels of MSI (MSI-H) were correlated with high TMB and immunocyte infiltration, which made dMMR-MSI-H CRC responsible for ICBs ( Alexander et al, 2001 ; Llosa et al, 2015 ; Ganesh et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that a 'mutator phenotype' associated with loss of mismatch repair pathways is a stronger predictor of outcome than quantity of mutations (109,110). Such tumors have increased T cell infiltrates counterbalanced by local immune suppression, including increased PDL1 expression (109,(111)(112)(113). However, it is unclear whether the mutations in these tumors dictates this infiltration phenotype.…”
Section: Role Of Antigen In Tissue Retentionmentioning
confidence: 99%
“…[17][18][19][20][21] The same types of tumors have different biological characteristics and different immune microenvironments, as is the case for colorectal and rectal cancers. 22 These differences directly affect responses to ICI treatment. [23][24][25][26] The main differences in the tumor microenvironments (TMEs) of dMMR/MSI-H, and pMMR/ MSS CRC patients are described below (Figure 1).…”
Section: Crosatellite S Tatus and Crc Immune Microenvironmentmentioning
confidence: 99%